2006
DOI: 10.1017/s0014479706003802
|View full text |Cite
|
Sign up to set email alerts
|

International Public Goods Through Integrated Natural Resources Management Research in Cgiar Partnerships

Abstract: The CGIAR System conducts research to produce international public goods (IPG) that are of wide applicability, creating a scientific base which speeds and broadens local adaptive development. Integrated natural resources management (INRM) research is sometimes seen to be very location specific and consequently does not lend itself readily to the production of IPGs. In this paper we analyse ways in which strategic approaches to INRM research can have broad international applicability and serve as useful foundat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…There are situations where NARES may lack sufficient capacity to promote certain techniques. Until this capacity is developed, IARCs may have a comparative advantage in carrying out promotion activities, as has been seen in many natural resource management research projects (Harwood et al, 2006). The case study showed that competition between the international centers and the national system can also result in constraints.…”
Section: Promotion Transactionsmentioning
confidence: 99%
“…There are situations where NARES may lack sufficient capacity to promote certain techniques. Until this capacity is developed, IARCs may have a comparative advantage in carrying out promotion activities, as has been seen in many natural resource management research projects (Harwood et al, 2006). The case study showed that competition between the international centers and the national system can also result in constraints.…”
Section: Promotion Transactionsmentioning
confidence: 99%
“…With its background in farming systems research, INRM seeks to build the capacity of farmers and other natural resources managers [40], while placing the farmer at the household or field level at the center of activities [41,42]. This is as strength in the approach, that when systems analysis is being conducted the farm level provides a tangible and practical boundary definition.…”
Section: Integrated Natural Resources Managementmentioning
confidence: 99%
“…In further descriptions of the approach the focus remains on the multitude of scales with the ecosystems as boundary of influence [39]. Hence ecosystems, or agroecosystems of varying sizes from plot level to ecozone or social units from the village to national level that cross scales and boundaries are discussed [42].…”
Section: Integrated Natural Resources Managementmentioning
confidence: 99%
“…Many developing countries where agriculture is relatively commercialised have seen increasing private sector investment in agricultural research (Naseem et al, 2010). This has forced the public sector -including the CGIAR -to re-frame its role in terms of the provision of 'public goods' (Anderson, 1998;Gardner and Lesser, 2003;Harwood et al, 2006;Lele and Gerrard, 2003). This evolving context also resulted in new emphasis on the creation of partnerships, alliances and 'learning platforms': the CGIAR Challenge Programmes, for example, clearly reflected these shifting institutional, funding and political landscapes, as does the increasing prominence of the language of 'publicprivate partnerships' in relation to international agricultural research Agriculture (Giller et al, 2011;Giller et al, 2009;Jenrich, 2011;Marongwe et al, 2011;Nkala et al, 2011;Owenya et al, 2011;Silici et al, 2011).…”
Section: Impacts On Agronomic Researchmentioning
confidence: 99%